Characterization of beta-cyclodextrin inclusion complexes containing an essential oil component. (1st April 2016) - Abarca, Romina L.; Rodríguez, Francisco J.; Guarda, Abel; Galotto, María J.; Bruna, Julio E.
Highlights: An inclusion complex of 2-nonanone with β-cyclodextrin was prepared. Different analysis confirmed the formation of inclusion complexes. The active compound 2-nonanone is fungistatic to Botrytis cinerea . Abstract: An important issue in food technology is that antimicrobial compounds can be used for various applications, such as the development of antimicrobial active packaging materials. Yet most antimicrobial compounds are volatile and require protection. In the present study, the inclusion complexes of 2-nonanone (2-NN) with β-cyclodextrin (β-CD), were prepared by a co-precipitation method. Entrapment efficiency (EE), thermal analysis (DSC and TGA), X-ray diffractometry (XRD), Fourier transform infrared spectroscopy (FT-IR), sorption isotherms and antifungal activity were evaluated for the characterization of the inclusion complex (β-CD:2-NN). A higher EE was obtained (34.8%) for the inclusion complex 1:0.5 than for other molar rates. Both DSC and TGA of the inclusion complexes showed the presence of endothermic peaks between 80 °C and 150 °C, attributed to a complexation phenomenon. Antimicrobial tests for mycelial growth reduction under atmospheric conditions proved the fungistatic behaviour of the inclusion complexes against Botrytis cinerea .